Bed bug bites mimicking bullous pemphigoid: a report of two cases - Aleksandra Wieczorek; Jacek Szepietowski; Katarzyna Łoza; Andrzej Bizoń; Julia Lanckorońska; Karolina Rutkowska; Katarzyna Głogowska (Termedia Publishing House, 2016)
Introduction . Bed bugs belong to the family Cimicidae, which includes two cosmopolitan species: Cimex lectularius and Cimex hemipterus. Bed bugs feed on the blood of humans and animals. As a result of bites, skin changes can manifest as itchy spots, erythematous-edematous lesions, hives and bullae. Aim . To describe two cases: a father and daughter living in the same household, both having skin lesions after bed bug bites that could imitate autoimmune bullous diseases. Case reports. The first case concerns a 57-year-old man on whose trunk and extremities were erythematous-edematous lesions and bullae. The second case concerns the 34-year-old daughter of the first patient, on whose trunk and extremities were linear erythematous-edematous lesions. Both in the first and second case direct and indirect immunofluorescence was negative. Conclusions. Bed bug bites can mimic other skin diseases, including autoimmune bullous diseases.